(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
The article discusses the socio-cultural aspects of stimulating the work of scientific and design activities. The definition of design activity is also given. The main features of stimulating the work of researchers are described, as well as recommendations for improving the effectiveness of incentives in research and development activities are given.